TERT Promoter Mutation Analysis to Distinguish Glioma From Gliosis. Issue 4 (29th January 2020) - Hewer, Ekkehard; Phour, Jaison; Gutt-Will, Marielena; Schucht, Philippe; Dettmer, Matthias S; Vassella, Erik
Abstract: Among the most challenging diagnostic issues in surgical neuropathology is the distinction between scant infiltration by diffuse gliomas and reactive gliosis. The best documented ancillary marker to establish a definitive diagnosis of glioma in this setting is the identification of hotspot mutations in the isocitrate dehydrogenase 1 and 2 ( IDH1/IDH2 ) genes, which is limited, however, by the low prevalence of these mutations in gliomas of elderly adults. Since telomerase reverse transcriptase ( TERT ) promoter mutations are present in the vast majority of IDH-wildtype diffuse gliomas, we hypothesized that combined analysis of IDH and TERT might overcome these limitations. For this purpose, we analyzed a series of non-neoplastic and neoplastic CNS samples for the prevalence of TERT hotspot mutations. TERT mutations were identified in none out of 58 (0%) reactive gliosis samples, and in 91 out of 117 (78%) IDH-wildtype gliomas. Based on a series of 200 consecutive diffuse gliomas, we found that IDH mutation analysis alone had a sensitivity of 28% (63% and 12%, respectively, in patients below and above age of 50) for detection of gliomas, whereas a combined analysis of IDH and TERT was 85% sensitive (87% and 84%, respectively, below and above age of 50). In sum, our findings suggest that TERT promoter mutation analysis contributes favorably to a molecular panel in cases equivocal for glioma versus gliosis on morphological grounds, especially in patients above age of 50, in which IDH analysis alone performs poorly.